(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
In this article, an algorithm (QKV) was developed that takes into account many factors in predicting the level of cardiovascular diseases, in particular, taking into account the relationships between factors. With the help of machine learning, the accuracy of the model has been increased, taking into account the complex interconnection of the data included in the MLP model. In addition, in the process of training the dataset processed through the QKV algorithm to the MLP model, it was possible to quickly achieve the minimum value of the Loss function and find the optimal weight coefficient.